1998
DOI: 10.1136/hrt.80.2.174
|View full text |Cite
|
Sign up to set email alerts
|

Coronary arterial anatomy in tetralogy of Fallot: morphological and clinical correlations

Abstract: Objective-To clarify the problems in angiographic diagnosis of major coronary arteries crossing the right ventricular outflow tract. Design-Aretrospectivestudywithclinicomorphological correlations to ascertain any aberrant coronary arteries and variations in distribution of the normal right coronary arterial branches. Setting-Tertiary referral centre. Subjects-36 necropsy specimens together with the aortograms and surgical reports from 130 patients with tetralogy of Fallot. Results-A preventricular branch was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
38
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 27 publications
0
38
0
Order By: Relevance
“…CMR is useful in defining congenital or inflammatory changes of the coronary arteries as in Bland-White-Garland syndrome, 62 and Kawasaki disease. [63][64][65] Congenital abnormalities in the course of the proximal coronary arteries can be reliably depicted by CMR both in patients with CHD (prevalence of 30% in CHD), 66 and especially tetralogy of Fallot, 67,68 and also in those with otherwise normal cardiac anatomy (1% of the general population). [69][70][71] CMR has advantages over X-ray angiography in clarifying the spatial relationship of these arteries with respect to the aorta and the pulmonary artery, which is crucial for estimating the risk associated with these abnormalities and for surgical planning.…”
Section: Congenital Heart Disease General Aspectsmentioning
confidence: 99%
“…CMR is useful in defining congenital or inflammatory changes of the coronary arteries as in Bland-White-Garland syndrome, 62 and Kawasaki disease. [63][64][65] Congenital abnormalities in the course of the proximal coronary arteries can be reliably depicted by CMR both in patients with CHD (prevalence of 30% in CHD), 66 and especially tetralogy of Fallot, 67,68 and also in those with otherwise normal cardiac anatomy (1% of the general population). [69][70][71] CMR has advantages over X-ray angiography in clarifying the spatial relationship of these arteries with respect to the aorta and the pulmonary artery, which is crucial for estimating the risk associated with these abnormalities and for surgical planning.…”
Section: Congenital Heart Disease General Aspectsmentioning
confidence: 99%
“…Although magnetic resonance imaging has been recognized as well suited to assess the detailed cardiac anatomy in postoperative patients with TOF, it has not been possible until recently to evaluate the three-dimensional anatomy of the whole heart and great vessels [3]. In addition, magnetic resonance imaging is not feasible for detecting anomalous coronary artery which frequently accompanies TOF [4] because of its limited spatial resolution. MDCT permits direct visualization of the whole coronary artery system with its high spatial resolution.…”
Section: Discussionmentioning
confidence: 99%
“…11 Our review of literature focusing on the coronary arterial anatomy in CCTGA has demonstrated that some patients had significant coronary abnormalities, [13][14][15] but interestingly this was less frequently than what has been observed in other common congenital cardiac lesions. [16][17][18][19] It is important to know of the presence of a coronary anomaly (in origin, course and distribution) in order to determine the optimal surgical approach and outcome. 11 Previous studies have suggested a consistently inverted coronary arterial pattern in patient with CCTGA and, rarely, a coronary ostium or artery.…”
Section: Discussionmentioning
confidence: 99%